The Chronic Heart-Failure Assistance by Telephone (CHAT) study: Assessment of telephone support for vulnerable patients with chronic disease - Yallop, J.; Chan, B.; Piterman, L.; Tonkin, A.; Forbes, A.; Davidson, Patricia; Clark, Chris; Halcomb, E.; Nangle, A.; Stewart, S.; Croucher, J.; Krum, H. (Blackwell Publishing, 2006)
Aim: To determine whether telephone support using an evidence-based protocol for chronic heart failure(CHF) management will improve patient outcomes and will reduce hospital readmission rates in patients without access to hospital-based management programs. Methods: The rationale and protocol for a cluster-design randomised controlled trial (RCT) of a semiautomated telephone intervention for the management of CHF, the Chronic Heart-failure Assistance by Telephone (CHAT) Study is described. Care is coordinated by trained cardiac nurses located in Heartline, the national call center of the National Heart Foundation of Australia in partnership with patients general practitioners (GPs). Conclusions: The CHAT Study model represents a potentially cost-effective and accessible model for the Australian health system in caring for CHF patients in rural and remote areas. The system of care could also be readily adapted for a range of chronic diseases and health systems.